Evaluation of the nanostructure of cervical third cementum in health and chronic periodontitis: An in vitro study - Subramoniam Sundaram; Rajagopalan Ramaseshan; Sitaram Dash; Suresh Ranga Rao (Wolters Kluwer Medknow Publications, 2014)
Background: During the progression of periodontal disease, the cementum undergoes alterations in its structure and composition. Understanding the nanostructure of cementum, in terms of its mechanical properties, will provide an insight into the milieu that periodontal ligament cells encounter in health and chronic periodontitis. This study aims to analyze the nanomechanical properties of the cervical third of the cementum (transverse section) in health and chronic periodontitis. Materials and Methods: Twenty teeth (10 healthy and 10 periodontally diseased) were collected and the nanomechanical properties of the transverse section of the cervical third cementum were evaluated with depth-sensing nanoindentation technique under dry conditions. A total of 100 nanoindentations were performed to analyze the modulus of elasticity and hardness of cervical third of the cementum. Results: The nanomechanical properties of the healthy cervical third cementum sections were significantly higher (P < 0.05) (hardness: 0.720 ± 0.305 GPa; modulus: 15.420 ± 3.902 GPa) than the diseased cementum section (hardness: 0.422 ± 0.157 GPa; modulus: 11.056 ± 3.434 GPa). Conclusion: The results of our study indicate that the hardness and modulus of elasticity of the cervical third cementum decreases significantly in chronic periodontitis.